(untitled) (Journal of Media studies, 2023)
This article contains researches about the definition of digitaltokens, types, history of origin and development, also contains detailedanalysis about the consistency of the digital tokens. Based on this, identifyadvantages and disadvantages, also suggest recommendations for protectinguser funds during trading operations and usage of purchased digital tokens.Theoretical significance of the research is to demonstrate existing and possiblelegal violations related to digital tokens. The practical significance of theresearch lies in the lack of clarity on the use of digital tokens in the socioeconomical aspects of society. For these purposes, research was carried out tostudy the theory and practical application of digital tokens from differentscientific points of view, especially covered by the economic and informationtechnology environment of application. And also, explore the possibilities ofusing digital tokens as an electronic means of payment. Research methods:comparative, historical, systematisation.